Safe use of MRI in people with cardiac implantable electronic devices. Issue 24 (29th September 2015) - Lowe, Martin D; Plummer, Christopher J; Manisty, Charlotte H; Linker, Nicholas J
Abstract : MR scanning in patients with cardiac implantable electronic devices (CIEDs) was formerly felt to be contraindicated, but an increasing number of patients have an implanted MR conditional device, allowing them to safely undergo MR scanning, provided the manufacturer's guidance is adhered to. In addition, some patients with non-MR conditional devices may undergo MR scanning if no other imaging modality is deemed suitable and there is a clear clinical indication for scanning which outweighs the potential risk. The following guidance has been formulated by the British Heart Rhythm Society and endorsed by the British Cardiovascular Society and others. It describes protocols that should be followed for patients with CIEDs undergoing MR scanning. The recommendations, principles and conclusions are supported by the Royal College of Radiologists.